Evaluasi Kapasitas Drainase di Jalan Mayjen HM Ryacudu Kota Palembang Menggunakan Pemodelan EPA SWMM - Ade Tricia Miranda; Hartini Hartini; Adji Sutama; Marice Agustini (Universitas Batanghari Jambi, 2026)
Flooding is a natural disaster that significantly disrupts human activities. The occurrence of flooding is closely related to drainage problems, as rainwater runoff requires a drainage system capable of collecting and conveying runoff water to drainage outlets. Jalan Mayjen HM Ryacudu in Palembang City frequently experiences flooding, even though the existing drainage system has an outlet that directly discharges into the Musi River. This study evaluated the drainage capacity along Jalan Mayjen HM Ryacudu due to the persistent flooding occurring in the area. The purpose of this evaluation was to determine an appropriate drainage capacity within the study area as a mitigation measure against flooding. The evaluation was conducted by simulating rainfall runoff using the EPA SWMM program. The results of the EPA SWMM modeling indicate that the existing drainage capacity is still unable to optimally accommodate and convey rainwater runoff, resulting in inundation at several locations along Jalan Mayjen HM Ryacudu. The mitigation scenario through drainage dimension optimization showed that modifying the drainage channels to a uniform size of 1.2 × 1.2 meters was able to eliminate flooding indications in the EPA SWMM simulation results.